Penyerapan Anggaran Belanja Langsung Pada Dinas Kesehatan Kabupaten Bandung - Sahya Anggara; Pilawati Pilawati (Department of Public Administration, 2019)
The purpose of this study is to analyze, study and find out how the absorption of direct expenditure budget at the Bandung District Health Office 2017 Fiscal Year. In measuring the budget absorption variable, the author uses Halim's theory of budget absorption which includes budget, budget absorption, supporting factors and obstacles to budget absorption. The research approach used is qualitative research type description. Data collection techniques were carried out by direct observation, in-depth interviews, and document studies. Data analysis techniques using the theory of Miles and Huberman which consists of three activities namely Data Reduction, Data Presentation, Drawing Conclusions. The results showed that based on three-dimensional indicators the absorption of direct budget in general has been going well. But there are still a number of things that need to be improved, namely regarding the approval of the budget that has not been timely, the lack of human resources (employees) and there are programs that have not been achieved effectively and efficiently so that it affects the absorption of direct expenditure that is not yet optimal. So that the Bandung District Health Office must make efforts to increase and optimize budget absorption by means of approving budgets in a timely manner, proposing an increase in the number of employees and conducting socialization to employees about the budget that will be used in carrying out any program activities that have been previously determined so that the absorption of the budget can be absorbed immediately optimally.